Cioko: Ritual Keagamaan dan Penguatan Identitas Masyarakat Tionghoa - Selviani, Shella; Rohmatin, Tien; Bustamin, Bustamin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
This research discusses the Cioko Prayer Ritual in the Chinese Community in Sewan Lebak Wangi, Tangerang City. This research has urgency in understanding the social, cultural and religious dynamics of the Chinese community and the meaning contained in the Cioko Prayer Ritual. The focus of this research is to describe and explore in depth the Cioko Prayer Ritual as one of the hereditary cultures of the Chinese Community in Sewan Lebak Wangi. The Qualitative Method with an Anthropological Approach is used in this study using observation-based data collection techniques, interviews and literature studies. The results of the study show that the Cioko Prayer Ritual is not only a religious ritual, but also a means of strengthening cultural and social identity. This ritual reflects the response of the Chinese community to the social changes that have occurred, they seek to maintain their cultural heritage in the midst of global modernization.